An experimental investigation into the behaviour of a 5 ton electric overhead travelling crane and its supporting structure - De Lange, Johan Hendrik (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2007.